Current Mental Health Clients’ Attitudes Regarding Religion and Spirituality in Treatment A National Survey - Oxhandler, Holly K.; Moffatt, Kelsey M.; Pargament, Kenneth I. 1950-; Pearce, Michelle J.; Vieten, Cassandra (2021)
Over the last several years, there has been a growing interest in clients’ views toward integrating their religion and spirituality (RS) into mental health treatment. However, most of these studies have been limited to small samples and specific populations, regions, and/or clinical issues. This article describes the first national survey of current mental health clients across the US regarding their attitudes towards integrating their RS in treatment using a revised version of the Religious/Spiritually Integrated Practice Assessment Scale-Client Attitudes, version 2 (RSIPAS-CAv2) with a sample of 989 clients. Our findings indicate mental health clients have overwhelmingly positive attitudes regarding integrating their RS into mental health treatment. Additionally, we explored what background characteristics predict clients’ attitudes toward this area of practice and found the top predictor was their intrinsic religiosity, followed by whether they had previously discussed RS with their current provider, age, gender, organized and non-organized religious activities, belief in God/Higher Power, and frequency of seeing their mental health provider. The reliability and validity of the RSIPAS-CAv2 was also explored and this scale is recommended for future use. Implications and recommendations for practice, research, and future training efforts are discussed.
Keywords: Anxiety; Attitudes; client preferences; Counseling; Depression; Mental Health; Psychiatry; Psychology; Religion; Social Work; Spirituality; Therapy